2012
DOI: 10.1007/s00268-012-1895-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cholestyramine Ointment in Reduction of Postoperative Pain and Pain during Defecation after Open Hemorrhoidectomy: Results of a Prospective, Single‐center, Randomized, Double‐blind, Placebo‐controlled Trial

Abstract: Compared with placebo, cholestyramine ointment (15%) reduced postoperative pain at rest and on defecation, and consequently lowered the analgesic requirement after open hemorrhoidectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 47 publications
0
21
0
1
Order By: Relevance
“…Several strategies have been proposed: acupuncture [7], creams or gels with several agents (nitrites, anesthetics, calcium antagonists, sucralfate, metronidazole, salsobromoiodic, cholestyramine) for topical application [8], [9], [10], [11], [12], [13], [14], [15], nonsteroidal anti-inflammatory suppositories [11], local infiltration with botulinum toxin [16], or local anesthetic agents [5], [6], [17] or even ambulatory PCA (patient controlled analgesia) pumps [18].…”
Section: Discussionmentioning
confidence: 99%
“…Several strategies have been proposed: acupuncture [7], creams or gels with several agents (nitrites, anesthetics, calcium antagonists, sucralfate, metronidazole, salsobromoiodic, cholestyramine) for topical application [8], [9], [10], [11], [12], [13], [14], [15], nonsteroidal anti-inflammatory suppositories [11], local infiltration with botulinum toxin [16], or local anesthetic agents [5], [6], [17] or even ambulatory PCA (patient controlled analgesia) pumps [18].…”
Section: Discussionmentioning
confidence: 99%
“…A number of ways have been attempted to relieve pain after a hemorrhoidectomy. For example, Ala et al [ 20 ] reported that cholestyramine ointment was effective against postoperative pain after a hemorrhoidectomy; the ointment group experienced less pain 12 and 48 hours after surgery than the control group did, and their pain completely disappeared 2 weeks later. Other effective treatments for the relief of postoperative pain, including preoperative lactulose [ 21 ], postoperative metronidazole [ 22 ], a left lateral anal sphincterectomy with hemorrhoidectomy [ 5 23 ], and botulinum injections, have been reported [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although therapeutic options of pruritus are available, the lack of well-conducted, randomized, controlled studies is an obstacle for the development of an effective and uniform treatment protocol. Cholestyramine is the most recommended first line therapy for pruritus[ 71 ], while rifampicin, opiate antagonists and sertraline have been utilized as second-, third-, and fourth-line therapies, respectively[ 72 , 73 ].…”
Section: Therapeutic Strategies Of Hcv-associated Pruritusmentioning
confidence: 99%